A systematic review on relationship between stress and problematic smartphone use - Boon Yew Wong; Kee Jiar Yeo; Lina Handayani (Intelektual Pustaka Media Utama, 2022)
This study systematically reviewed the existing research on relationship between stress and problematic smartphone use. It aimed to provide an aggregative view of the existing research findings on relationship between stress and problematic smartphone use and how these researches are conducted (i.e., research designs, sampling techniques, sample characteristics, measurement scales, data analysis techniques). A thorough literature research in five bibliographic databases (Taylor & Francis, Wiley, SAGE, SpringerLink, ScienceDirect), Google Scholars, and previous review papers has resulted in 35 studies being included in this review. This review has found that the existing empirical evidence generally demonstrated that i) stress can cause problematic smartphone use; ii) the effect of stress on problematic smartphone use is not straightforward but transmitted by other variables (i.e., mediator), and iii) the effect of stress on problematic smartphone use varies as a function of context or individual differences (i.e., moderator). Finally, following a thorough review of their methodological information, this review has also identified the strengths and limitations of the existing studies on relationship between stress and problematic smartphone use, as well as potential directions of research.